Assessment of energy potential of municipal solid waste from university of derby student residence - Gukop, N. S.; Japhet, J. A.; Lengs, B. D.; Adesanmi, A. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2021)
Solid waste generated from the University of Derby Student Residence was used to examine the amount of thermal energy that can be reclaimed from the waste. The waste material used for the analysis was categorized into different constituents which were used for analyzing the sample, from which the recoverable energy was estimated. The calorific value of the waste mixture was found to be 34.28 MJ/kg with a corresponding thermal energy recoverable estimated to be 1532.96 MJ/day, which gave an equivalent power of 425.82 kWh/day. The findings from this study suggests the necessity for the adoption of waste management systems that will integrate energy recovery from wastes in order to supplement the increasing demand for energy.